The androgen receptor amino-terminal domain: structure, function and therapeutic potential - Hunter, Irene; Jamieson, Craig; McEwan, Iain J (Endocrine oncology, 2025)
Signalling by the steroid hormone testosterone involves the androgen receptor (AR), a structurally dynamic protein. The amino-terminal domain of the AR makes up more than half of the protein and has been found to be intrinsically disordered. This structural plasticity mediates receptor-dependent transcription, intradomain interactions and allosteric regulation. AR activity is a primary drug target in advanced and metastatic prostate cancer, a leading cause of cancer-related death in men. Recent research has focused on the amino-terminal domain as a novel drug target. In this review, we discuss the structural properties of the receptor and highlight some promising preclinical and clinical studies that aim to develop a drug discovery pipeline of small-molecule inhibitors targeting the amino-terminal domain.